2017
DOI: 10.1039/c7mt00014f
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin resistance in cell models: evaluation of metallomic and biological predictive biomarkers to address early therapy failure

Abstract: Cisplatin, one of the most extensively used metallodrugs in cancer treatment, presents the important drawback of patient resistance. This resistance is the consequence of different processes including those preventing the formation of DNA adducts and/or their quick removal. Thus, a tool for the accurate detection and quantitation of cisplatin-induced adducts might be valuable for predicting patient resistance. To prove the validity of such an assumption, highly sensitive plasma mass spectrometry (ICP-MS) strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
(92 reference statements)
2
9
0
Order By: Relevance
“…These results suggest that either the adducts are more efficiently repaired than those generated by cisplatin and/or their covalent binding to DNA is less efficient [ 62 ]. Interestingly, in contrast to cisplatin, the amount of Pt-ttpy and Pt-tpy uptake was the same in both cell lines, but the amount of complexes bound to DNA was reduced in A2780cis cells, suggesting a more efficient repair mechanism in A2780cis cell lines as already reported [ 63 ].…”
Section: Resultssupporting
confidence: 71%
“…These results suggest that either the adducts are more efficiently repaired than those generated by cisplatin and/or their covalent binding to DNA is less efficient [ 62 ]. Interestingly, in contrast to cisplatin, the amount of Pt-ttpy and Pt-tpy uptake was the same in both cell lines, but the amount of complexes bound to DNA was reduced in A2780cis cells, suggesting a more efficient repair mechanism in A2780cis cell lines as already reported [ 63 ].…”
Section: Resultssupporting
confidence: 71%
“…Cisplatin is one of the most commonly used chemotherapies in gynecologic oncology. Unfortunately, many cancers initially respond well to platinum treatment but often develop resistance when tumors recur . Until now, studies have shown that increased DNA repair, altered cellular accumulation, and increased drug inactivation are the main reasons for cells to acquire drug resistance .…”
Section: Discussionmentioning
confidence: 99%
“…The analysis can include essential trace metals and metalloids that contribute to different physiological processes and toxic metals that interfere with them. ICP-MS metallomics in cancer research has been used for the evaluation of the pharmacokinetics and toxicity of approved and proposed metallo-drugs (platinum, ruthenium, and nanoparticle-based drugs) [94][95][96]. Noninvasive techniques like positron emission tomography (PET) scans have been also used to identify global or localized flux of metals like Cu and Fe, relevant in altered cancer metabolism [97,98].…”
Section: Metallomicsmentioning
confidence: 99%